Penerapan Nilai-Nilai Islam dalam Etika Profesi Kesekretariatan di Lembaga Pendidikan Islam - Makmur, Makmur; Gusvita, Maisarah; Robi'ah, Robi'ah; Rahmawati, Dyah; Muslimin, Muslimin; Abdullah Aji, Yunita (Al-Fikrah, 2025)
The implementation of Islamic values in the professional ethics of secretarial work in Islamic educational institutions is a crucial aspect in establishing a professional work environment based on Islamic morality. This study aims to analyze the concept of Islamic values in professional ethics, its implementation in secretarial work within Islamic educational institutions, the challenges encountered, as well as the solutions and strategies for its reinforcement. The research method employed is a qualitative approach with a literature review as the primary source. The findings indicate that Islamic values, such as honesty, trustworthiness, responsibility, discipline, and professionalism, serve as the fundamental principles of professional ethics in secretarial work. The implementation of these values is evident in administrative, communication, and service aspects, all of which adhere to Sharia principles. However, several challenges exist in its application, including a lack of understanding of Islamic ethical concepts, the influence of modernization, and weak supervision systems. Therefore, effective strategies are needed, such as specialized training, a Sharia-based management system, and regulatory reinforcement, to strengthen the application of professional ethics based on Islamic values. With optimal implementation, the secretarial profession in Islamic educational institutions can operate professionally, with integrity, and contribute positively to the development of Islamic education.